The consequences of the Artavia Murillo’s sentence in Peru and the conceived child - Suárez Gómez, María Isabel (2019)
The sentence issued by the Inter-American Court of Human Rights (IN/A Court HR), in the proceeding followed by Artavia Murillo and others against the State of Costa Rica, has already legal consequences in Peru, corresponding to the right to life of conceived child. Indeed, the aforementioned sentence has been the subject of jurisdictional pronouncements in Peru, which indicate that it must apply, without considering that the criterion taken on the beginning of the right to life of the conceived child, originates the ignorance of the early days of his or her existence and, therefore, contravenes the Constitution. The cases, which are still in discussion in court, refer to controversial issues such as emergency oral contraception and therapeutic abortion, which cannot be considered sexual and reproductive rights, when the life of the most defenseless subjects of the law is threatened: the conceived child.